2019
DOI: 10.1371/journal.pone.0221971
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus, pre-pregnancy body mass index, and gestational weight gain as risk factors for increased fat mass in Brazilian newborns

Abstract: Background Gestational diabetes mellitus (GDM) is a common complication of pregnancy. It may predispose offspring to increased fat mass (FM) and the development of obesity, however few data from Latin America exist. Objective To investigate the influence of GDM on newborn FM in mother-newborn pairs recruited from a public maternity care center in São Paulo, Brazil. Methods Data were collected cross-sectionally in 2013–2014 from 72 mothers dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
9
1
Order By: Relevance
“…Our findings of the impact of ppBMI were consistent with those who reported a positive association between ppBMI and %FM at birth [ 7 , 35 ] and others who did not find significant associations at 3 months [ 36 ], 5 months [ 6 ] and 6 months [ 36 ]. However, the positive association between ppBMI and FM/FFM p at birth, showed by Abreu et al [ 26 ], was not evident in our study. Conversely, some researchers have shown that ppBMI is not associated with FM or %FM, even in newborns [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings of the impact of ppBMI were consistent with those who reported a positive association between ppBMI and %FM at birth [ 7 , 35 ] and others who did not find significant associations at 3 months [ 36 ], 5 months [ 6 ] and 6 months [ 36 ]. However, the positive association between ppBMI and FM/FFM p at birth, showed by Abreu et al [ 26 ], was not evident in our study. Conversely, some researchers have shown that ppBMI is not associated with FM or %FM, even in newborns [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, recent research has demonstrated that FMI is a more reliable index than %FM when assessing neonatal adiposity [ 48 ]. In contrast, some studies [ 26 , 47 ] have suggested that an appropriate index should adjust the originator of the risk (FM) for a variable that is bearing the risk (FFM), thus recommending the index of FM/FFM p ; however, to the best to our knowledge, only one study [ 26 ] used FM/FFM p to identify maternal predictors of infant adiposity at birth. Our data demonstrate that FM/FFM p is highly sensitive to rapid changes in adiposity during this critical period of growth, with drastic increases from birth (~36) to 6 months (~1500).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also confirmed that maternal prepregnancy overweight and obesity were associated with an increased risk of LGA, independent of GDM subtypes. Studies in different races have reported that newborn body weight was positively correlated with maternal adiposity, 10,25 which is reflected as higher maternal pre‐BMI and GWG. Our study found that excessive GWG was not associated with increased risk of LGA, which may be due to the doctors' recommendation of weight gain control for women with GDM.…”
Section: Discussionmentioning
confidence: 99%